CHRISTOPANGANISM: A RELIGION IN SEARCH OF RELEVANCE OR A CONTEXTUALIZED CHRISTIANITY IN NIGERIA? - Amos Francis Dike (International Studies Journal)
The African belief in ancestral curses and witchcraft/witches constitutes a constant and permanent source of fear and anxiety to most Christians. A passing look at African Christianity suggests a Christopaganism kind of religion – a branded Christianity that is subsumed in African Traditional practices in search of meaning and relevance. This study attempts to study the nature, reasons for its emergence, and manifestation(s) of Christopaganism and its implications on Christianity in Africa. The research adopts conceptual and phenomenal approaches. Sourced data was philosophically and theologically analyzed. The study discovers that while the early missionaries left their converts battling with African traditional mythology. However, some contemporary Christians/pastors have an approach that can best be described as Christopaganism on order to bridge the gap created by western missionary exploit.Hence, while recognizing the existence of generational curses and magic, some Christian bodiesviews Christopaganismboth as a means of contextualizing Christianity and at the same time finding relevance. Thus, to retain the authentic Christianity in Africa that will at the same time have global relevance, African church should harmonize her beliefs and practices in line with the biblical Christianity. She must seek to return to a God-Christ-centered message where the price paid by Jesus Christ is sufficient to be projected at the expense of all human sacrifice, dilemma, and family predicaments.